Vaccination status and its determinants among children aged 12-23 months in Tigray, northern Ethiopia: A zero-inflated Poisson regression analysis. - Hailay Gebretnsae; Brhane Ayele; Fana Gebresilassie; Tsegay Hadgu; Hayelom Kahsay; Asfawosen Aregay; Kiros Demoz; Mulugeta Tilahun; Ataklti Gebretsadik; Znabu Hadush; Liya Mamo; Tsegay Wellay; et al. (PLoS ONE, 2025)
Background In Tigray, immunization services have been severely interrupted, and cases with vaccine preventable diseases become rampant due to the conflict. However, there is limited evidence on the status of child vaccination in the region. Therefore, this study aimed to assess the vaccination status and its determinants among children aged 12-23 months in Tigray, northern Ethiopia. Methods A community-based cross-sectional study was conducted in August 2023 in the Tigray region, Northern Ethiopia. Using a multistage cluster sampling technique, the study included mothers of children aged 12-23 months from 19 randomly selected districts. Data were collected through a pre-tested structured questionnaire designed on Open Data Kit (ODK). Child vaccination status (the outcome variable) was measured for 14 vaccine antigens. Data analysis was conducted using R software. A zero-inflated Poisson regression model was applied to identify factors associated with child vaccination status, with statistical significance determined at a p-value of < 0.05. Results In this study a total of 1,620 mothers of children aged 12-23 months were included. The overall proportion of fully vaccination was 59.9% (95% Confidence Interval (CI): 57.7-62.3%), while 29.4% (95% CI: 27.1-31.7%) were under-vaccinated and 10.7% (95% CI: 9.1-12.2%) were zero-dose. Being with no formal education(Adjusted Incidence Relative Risk (AIRR) = 0.94, 95% CI: 0.90-0.97), availability of routine immunization services at the nearest health facility (AIRR = 1.09, 95% CI: 1.04-1.13) and having media exposure (AIRR = 1.04, 95% CI: 1.01-1.08) were the factors associated with getting more vaccines among children. Moreover, being with no formal education (Adjusted Odds Ratio (AOR) =1.83, 95% CI: 1.21-2,75), availability of routine immunization services at the nearest health facility (AOR = 0.39, 95% CI: 0.27-0.55) and having Postnatal Care (PNC) follow-up (AOR = 0.53, 95% CI: 0.29-0.99) were the determinants for zero-dose vaccination. Conclusions This study revealed that a significant proportion (40.1%) of children were left as zero-dose or under-vaccinated. To improve vaccination coverage in post-conflict settings, health policymakers should prioritize re-building immunization infrastructure and ensuring the availability of vaccination services across all levels of the healthcare system through mobilizing and allocating resources. Media campaigns should be provided to encourage mothers to vaccinate their children. Healthcare professionals should also promote timely post-natal care visits to initiate vaccinations at the appropriate age. Furthermore, it is essential to identify and reach zero-dose or under-vaccinated children through targeted catch-up vaccination efforts to ensure that no child is left unvaccinated in post war settings.